Disability assessment due to stroke - Ertem, Uğur (The European Research Journal, 2023)
Objectives: The main purpose of the study is to determine the frequency of stroke in patients who applied to the disability board. The secondary aim of the study is to determine the factors affecting disability rates in patients who applied to the disability board due to stroke. Methods: Patients over the age of 18 who applied to the physical nedicine and rehabilitation outpatient clinic for disability assessment were included in the study. Disability board files of all patients were scanned retrospectively and the information obtained was recorded. Results: It was found that 9.1% of patients who were evaluated for disability and were found to have any level of disability experienced disability due to stroke. A statistically significant relationship was found between stroke-related disability score and advanced age, female gender, and the presence of aphasia and dementia in the patients (p < 0.05). However, no statistically significant relationship was found between the type of stroke, the affected side and the stroke-related disability scores (p > 0.05). Conclusions: Stroke patients constitute a remarkable part of disability assessment. When evaluating stroke patients in terms of their disability, comorbid diseases and demographic characteristics of the patients should also be taken into consideration.